Plectin-mediated cytoskeletal crosstalk as a target for inhibition of hepatocellular carcinoma growth and metastasis - Outla, Zuzana; Oyman-Eyrilmez, Gizem; Korelova, Katerina; Prechova, Magdalena; Frick, Lukas; Sarnova, Lenka; Bisht, Piyush; Novotna, Petra; Kosla, Jan; Bortel, Patricia; Borutzki, Yasmin; Bileck, Andrea; et al. (eLife, 2025)
The most common primary malignancy of the liver, hepatocellular carcinoma (HCC), is a heterogeneous tumor entity with high metastatic potential and complex pathophysiology. Increasing evidence suggests that tissue mechanics plays a critical role in tumor onset and progression. Here, we show that plectin, a major cytoskeletal crosslinker protein, plays a crucial role in mechanical homeostasis and mechanosensitive oncogenic signaling that drives hepatocarcinogenesis. Our expression analyses revealed elevated plectin levels in liver tumors, which correlated with poor prognosis for HCC patients. Using autochthonous and orthotopic mouse models we demonstrated that genetic and pharmacological inactivation of plectin potently suppressed the initiation and growth of HCC. Moreover, plectin targeting potently inhibited the invasion potential of human HCC cells and reduced their metastatic outgrowth in the lung. Proteomic and phosphoproteomic profiling linked plectin-dependent disruption of cytoskeletal networks to attenuation of oncogenic FAK, MAPK/Erk, and PI3K/Akt signatures. Importantly, by combining cell line-based and murine HCC models, we show that plectin inhibitor plecstatin-1 (PST) is well-tolerated and potently inhibits HCC progression. In conclusion, our study demonstrates that plectin-controlled cytoarchitecture is a key determinant of HCC development and suggests that pharmacologically induced disruption of mechanical homeostasis may represent a new therapeutic strategy for HCC treatment.
Keywords: nádory jater; signální transdukce; Signal Transduction; cytoskelet; Humans; plectin; therapeutic strategy; modely nemocí na zvířatech; metastasis; lidé; Liver Neoplasms; zvířata; proliferace buněk; myši; cancer biology; cytoskeletal crosstalk; Mice; cell biology; plecstatin; plektin; mouse; Neoplasm Metastasis; metastázy nádorů; Cell Proliferation; hepatocellular carcinoma; nádorové buněčné linie; Animals; Cell Line, Tumor; Disease Models, Animal; Plectin; Cytoskeleton; Carcinoma, Hepatocellular; hepatocelulární karcinom